The Effect of Modified Tabata Training and Leg Muscle Strength on Sickle Kick Speed - Umar, Uswatul Hasanah; Sumartiningsih, Sri; Rahayu, Setya (Journal of Physical Education and Sports, 2023)
The background is the speed of sickle kick pencak silat in PPLP South Sulawesi is minimum. It’s make during match easly to catch the opponents. The purpose is to determine the effect of modified tabata training and leg muscle strength on the sickle kick speed of PPLP South Sulawesi Pencak Silat athletes. Research method using experimental 2x2 factorial design and the sample is PPLP and SMANKO South Sulawesi pencak silat athletes totaling 12 people conducted in the training hall of PPLP South Sulawesi pencak silat athletes on April 30, 2023 to June 04, 2023. The exercises given were modified tabata training interval 1:½ and 1:1 for 5 weeks. Data collection techniques using leg dynamometer tests and sickle kick speed test for 10 seconds. The results of first hypothesis test show difference in the increase mean is 2.83, standar deviation is 1.095 and p value is 0.001 <0.05. Second hypothesis test show difference in the increase mean is 0.5, standar deviation is 0.928 and p value is 0.001 <0.05. Third hypothesis test show interaction between modified tabata training and leg muscle strength with p value 0.032 <0.05. The conclusion is athletes who are trained in modified tabata training 1:½ intervals and have good leg muscle strength have a better increase in sickle kick speed than athletes who are trained in modified tabata training 1:1 intervals and have moderate leg muscle strength, and there is an interaction between modified tabata training and leg muscle strength on sickle kick speed.